EFFECTIVENESS OF THE ONLINE DEMONSTRATION METHOD ON STUDENTS LEARNING OUTCOMES IN INFORMATION AND COMMUNICATION TECHNOLOGY THROUGH A QUASI-EXPERIMENTAL STUDY IN AN INDONESIAN JUNIOR SECONDARY SCHOOL - Cahyani Akbar Enduran; Anggara Sukma Ardiyanta; Farid Sukmana (JoEICT (Jurnal of Education And ICT), 2026)
Information and communication technology (ICT) education in In-donesian junior secondary schools has traditionally relied on lec-ture-based instruction, a format that affords learners limited oppor-tunity for active engagement and often fails to translate into optimal learning outcomes. This study investigated whether an online-adapted demonstration method produced significantly different learning outcomes compared with a conventional lecture-based method among grade VII students studying basic Microsoft Word operations at a public junior secondary school (SMPN 2 Pakel) in Tulungagung, Indonesia, during the transition to remote instruction necessitated by the COVID-19 pandemic. A quantitative, quasi-experimental approach employing a nonequivalent pretest-posttest control-group design was adopted. From a population of 94 grade VII students, 62 students were selected through purposive sampling and assigned to an experimental class (n = 31), which received vid-eo-based demonstration instruction distributed through a class mes-saging group and a video-sharing platform, and a control class (n = 31), which received conventional text- and lecture-based instruction through the same digital channels. Achievement was measured us-ing a validated multiple-choice test administered before and after treatment, and an independent-samples t-test was used to examine between-group differences once normality and homogeneity as-sumptions were confirmed. The mean posttest score of the experi-mental group (M = 83.06, SD = 7.49) exceeded that of the control group (M = 65.65, SD = 9.46); the independent-samples t-test indi-cated a statistically significant difference, t(60) = 8.035, p < .001, mean difference = 17.42. These findings demonstrate that the online demonstration method produced a significantly larger improvement in learning outcomes than the conventional method, supporting multimedia- and constructivist-learning perspectives that visual-ized, sequential demonstration facilitates deeper comprehension of procedural ICT content even in a fully remote setting. The study contributes empirical evidence on adapting an inherently visual, hands-on teaching method to emergency remote instruction—an area that remains underexplored relative to research on demonstra-tion teaching in face-to-face classrooms. Implications for ICT peda-gogy, methodological limitations, and directions for future research are discussed